Relações socioambientais no extrativismo da aroeira (Schinus terebenthifolius Raddi no baixo São Francisco SE/AL) - Jesus, Nádia Batista de (2010)
The waves of modernity linked to the regional development projects in the low part of São Francisco river have not so far meant the rising of social justice and citizenship for local communities, there arising rather a picture of environmental deterioration, social inequalities and subjects living in risk situation. For these artisanal fishers, who have been practicing the extractivism of aroeira (Schinus terebenthifolius Raddi) for eight years, the species has become an income source, as well as a goal of industries located in Espirito Santo which export and process its fruit, the so-called pink pepper . This research aimed to analyse the socioenvironmental aspects related to the process starting with extractivism and leading up to the transformation in pink pepper in the low parto of São Francisco river, describing the extractivist process prevailing there; it unveils the socioeconomic importance of aroeira extractivism for the artisanal fishers in the region; it identifies the production chain of aoreira in the low part of São Francisco river and tipifies the socioenvironmental conflicts originating in the extractivism of aroeira in the low part of São Francisco river. It is a case study with a qualitative focus whose data analysis is based in hermeneutics from pre interpretation by subjects to the reinterpretation of researcher, combining multiple theoretical, methodological and data approaches, and participation methods alike. The research found out that pink pepper is especially used in food and cosmetics industry, being production chiefly exported to European Union, United States, Canada and Argentina. Such demand causes an unceasing search for new areas of natural occurrence of the species. In this case, it has been integrated into the production chain the municipalities of the low part of São Francisco river: Santana do São Francisco Saúde and Brejo Grande counties Brejão dos Negros county, Pacatuba, Ilha das Flores, in Sergipe, and Piaçabuçu Peba and Sudene counties, in Alagoas. On one hand, the results of intentional extractivism and corporate practice are socioenvironmental conflicts involving different subjects . On the other hand, the pressure on resources leads to environmental degradation, a negative externality stemming from not following technical guidelines, causing areas which should be preserved to become environmentally unsustainable. In exporting markets, pink pepper reaches up to US$ 14/18 while the extractivist gets R$ 1,50 per kilo. In this context, capitalistic structural relations only partially pervades subjects´social life, including them in the production process while alienate them from that of capital growth, a result of economic rationality which turns nature into merchandise. Poverty is a strong factor behind environmental degradation, which causes socioenvironmental conflicts in the low part of São Francisco river (SE/AL). For extractivist fishers such a practice comes as an alternative to family income, which is accepted because of the lack of opportunities to provide for family needs in face of failing fishing in the region. Thus, aroeira (Schinus terebenthifolius Raddi) could be part of a proposal of sustainable development for the region. Especially so if one considers the immense poverty prevailing in the collecting areas, where new managing practices have been introduced which include the participation of local communities so as to improve surviving conditions.